(untitled) (Eurasian Journal of Humanities and Social Sciences, 2022)
In this article the author analyses the issues of formation of legal consciousness and legal culture of young people, and consistently and contradictorily reveals different aspects of the formation of legal consciousness in the same category of the population, taking into account the specifics of this process.